Phytosanitary investigations on the invasive and vectorial impact on apple cultivation in the environmental conditions of the Republic of Moldova - Alexei Bivol; Ștefan Rusu; Elena Iurcu-Străistaru; Viorelia Rusu (Acta et Commentationes Exact and Natural Sciences, 2025)
In this study, bioecological and taxonomic investigations were conducted on the populations of invasive and vectorial parasitic nematodes associated with apple cultivation in intensive orchards. The purpose of the research was to establish a comparative analysis and assess the diversity of nematode complexes with parasitic and vectorial impacts on apple crops from various horticultural regions, aiming to identify the most dangerous species with harmful effects on productive apple orchards. The objectives of the study focused on highlighting the most invasive species of nematodes and virus vectors from the orders Tylenchida and Dorylaimida associated with apple cultivation. The research confirmed the presence of 15 species of invasive and vectorial nematodes with parasitic impacts, which cause viral diseases in the studied sectors. Additionally, comparative estimates of the nematode population density were made, and 13 associated viral diseases were identified, with symptomatic features and varying degrees of infection.